Adipocyte lipopolysaccharide binding protein (LBP) is linked to a specific lipidomic signature. Issue 2 (21st December 2016) - Moreno‐Navarrete, José María; Jové, Mariona; Padró, Teresa; Boada, Jordi; Ortega, Francisco; Ricart, Wifredo; Pamplona, Reinald; Badimón, Lina; Portero‐Otín, Manuel; Fernández‐Real, José Manuel
Abstract : Objective: Lipopolysaccharide binding protein (LBP) is part of a family of structurally and functionally related lipid transfer proteins. This study aimed to investigate the associations of LBP with the lipid composition of human adipose tissue. Methods: Lipidomic analysis was performed in whole adipose tissue. To validate the associations found, LBP was knocked down (KD) in 3T3‐L1 adipocytes, and lipidomic profile was evaluated by nontargeted lipidomics. Results: LBP gene expression was negatively associated with phosphatidylcholine, phosphatidylserine, and sphingomyelin relative abundance in vivo . LBP expression was also decreased in those samples with the highest docosahexanoic content, implicated in the resolution of inflammation. The KD of LBP (by ∼70%) led to sharp changes in the lipidome of adipocytes. Of note, specific plasmalogen species PE(O‐16:0/22:5), PE(38:2), odd chain glycerolipids, and cholesteryl linoleate were upregulated by LBP KD. In contrast, GM3 gangliosides, several ceramides, a triacylglycerol potentially containing arachidonate, and cholesteryl palmitate were downregulated by LBP KD. Conclusions: LBP seems to play a role in the regulation of lipid composition of adipose tissue linked to resilience to inflammation.